β-adrenergic signaling modulates breast cancer cell mechanical behaviors through a RhoA-ROCK-myosin II axis - Tae-Hyung Kim; Minh-Tam Tran Le; Mijung Oh; Esteban Vazquez-Hidalgo; Bryanna Chavez; Donald M. Lamkin; Alexander Abdou; Xing Haw Marvin Tan; Alexei Christodoulides; Carly M. Farris; Changhoon Lee; Pei-Yu Chiou; et al. (iScience)
Summary: The ability of cancer cells to deform and generate force is implicated in metastasis. We previously showed that β-adrenergic agonists increase cancer cell stiffness, which was associated with enhanced motility and invasion. Here, we investigate how β-adrenoceptor (βAR) activation alters the mechanical behaviors of triple-negative breast cancer cells. We find that βAR activation increases traction forces in metastatic MDA-MB-231HM and MDA-MB-468 cells, but not in non-tumorigenic MCF10A cells. Using computational modeling, we show that βAR activation increases the number of active myosin motors via myosin light chain phosphorylation. To identify molecular regulators, we use a deformability assay to screen for pharmacologic and genetic perturbations. Our results define a βAR-RhoA-ROCK-non-muscle myosin II (NMII) signaling axis that modulates the mechanical behaviors of MDA-MB-231HM and MDA-MB-468 cells. These findings provide insight into how stress signaling regulates cancer cell mechanics and suggest potential targets to block metastasis in triple-negative breast cancer.